Worms Propagation Modeling and Analysis in Big Data Environment. (5th October 2015) - He, Song; Zhang, Can; Guo, Wei; Zhai, Li-Dong
The integration of the Internet and Mobile networks results in huge amount of data, as well as security threat. With the fragile capacity of security protection, worms can propagate in the integration network and undermine the stability and integrity of data. The propagation of worm is a great security risk to massive amounts of data in the integration network. We propose a kind of worm propagating in big data environment named BD-Worm. BD-Worm consumes computing resources and gets privacy information of users, which causes huge losses to our working and living. This paper constructs an integration network topology model and designs the BD-Worm propagating in the big data environment. To analyze the propagation of BD-Worm, we conduct a simulation and provide some recommendations to contain the widespread of BD-Worm according to the simulation results.